Unstart phenomena induced by mass addition and heat release in a model scramjet. (24th May 2016) - Im, S.; Baccarella, D.; McGann, B.; Liu, Q.; Wermer, L.; Do, H.
Abstract : The unstart phenomena in a model scramjet with a free stream Mach number of 4.5 were investigated at an arc-heated hypersonic wind tunnel. High-speed schlieren imaging and high resonance frequency pressure measurements were used to capture the flow features during the unstart process. Three unstart conditions were tested: (i) a low-enthalpy free stream with mass loading, (ii) a high-enthalpy free stream with mass loading and (iii) a high-enthalpy free stream with mass loading and heat release. It was revealed that the unstart threshold and the time from the onset to the completion of unstart depended strongly on the mass loading rate and the heat exchange. The negative heat addition (cooling) significantly increased the threshold of mass flow rate triggering unstart. The decrement of the mass flow rate threshold for unstart was observed in the presence of heat release by combustion. The observed transient and quasi-steady behaviours of the unstart shockwave system and the jet motion were similar in all of the test conditions. On the other hand, at the lip of inlet model, the unstart shockwave under the cold free stream condition exhibited a relatively steady behaviour while severe oscillatory flow motions of the jet and the unstart shockwave were observed in the combustion-driven unstart process. The different unstarted flow behaviours between the three flow conditions were explained using a simplified one-dimensional flow choking analysis and use of the Korkegi criterion.